THE ROLE OF WORK DISCIPLINE, FACILITIES, AND WORK ENVIRONMENT IN EFFORTS TO INCREASE EMPLOYEE PERFORMANCE - Manda HM; Sultan Iskandar; Husnawati Rahman (Bajang Institute, 2022)
The problem faced by PT. Sarana Sinar Sulawesi, especially in the production department, is the low performance of its employees. This research aims to determine the effect of work discipline, facilities, and work environment on employee performance at PT. Sarana Sinar Sulawesi. This research is quantitative, using primary data and secondary data. The total population of 127 employees, with the sample using as many as 91 people. The data analysis method used multiple linear regression. The study results show that partially work discipline, facilities, and work environment positively affect employee performance, as indicated by the number of positive counting results. Simultaneously, work discipline, facilities, and work environment also positively affect employee performance.